Books of blood. Volume one - Barker, Clive, 1952- (Berkley, 2020)
Everybody is a book of blood; wherever we're opened, we're red. In this collection of disturbing tales, Clive Barker combines the extraordinary with the ordinary, bringing to life our darkest nightmares with stories that both seduce and devour.